TASAWUF FALSAFI - Abrar M. Dawud Faza (UIN Sumatera Utara, 2019)
Philosophical Sufism has emerged clearly in Islamic treasures since the sixth century Hijrah even though the characters were only known later in the century. Since then, this type of Sufism lived and developed, especially among Sufis who were also philosophers, until near lately. The existence of a combination of Sufism and philosophy in philosophical Sufism teachings led to the teachings of Sufism of this type mixed with a number of philosophical teachings outside of Islam, such as Greece, Persia, India, and Christianity. However, his originality as Sufism still does not disappear.Keywords: Sufism, Philosophy